The self naturalism, consciousness, and the first-person stance - Ganeri, Jonardon (Oxford : Oxford University Press, 2012)
Jonardon Ganeri presents a study of selfhood, drawing on Indian theories of consciousness and mind. He explores the notion of embodiment and the centrality of the emotions to the self, and shows how to harmonize the idea of the first-person perspective with a naturalist worldview which encompasses the normative.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Self (Philosophy); Philosophy of mind; Naturalism